Periphyton Community on the Ceramic Substrate Around the Floating NetCage PLTA Koto Panjang Reservoir Kampar Regency Riau Province - Beta Posmarito Pardede; Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT Periphyton is microorganism that live attached to submerged substrate. In the vicinity of Koto Panjang Dam Site there are fish farming activities in floating net cages, which produce feed residu and metabolic waste. This research aims to determine periphyton community around the Dam Site of the Koto Panjang Reservoir. This research was conducted in December 2020. There were 3 stations, namely station 1 (less KJA), station 2 (moderate KJA), and station 3 (full KJA). The subtrate used is ceramic substrate with a size (8x3 cm2). Substrate was planted 1 week before sampling. Sampling were conducted 3 times at once a week. The periphyton samples were obtained by spraying the surface of ceramic substrate with aquadest using a plastic sprayer. Periphyton were preserved with lugol 1%, then identified and abundance counted. Water quality parameters measured were temperature, transparency, pH, dissolved oxygen, free carbondioxide, nitrate, and phosphate. Results shown that there were 36 types of periphyton, belongs to 7 classes, namely Bacillariophyceae (6 types), Chlorophyceae (17 types), Cyanophyceae (3 types), Trebouxiphyceae (4 types), Zygnematophyceae (4 types), Euglenophyceae (1 type), dan Dinophyceae (1 type). Periphyton abundance during the study ranged from 2.479-10.357 cells/cm2. Two way anova test on the number of species and periphyton abundance around the Dam Site of PLTA Koto Panjang Reservoir showed that the number and abundance of periphyton were not significantly diffrerent between stations and between times. Keywords:Periphyton, PLTA Koto Panjang Reservoir, Ceramic Substrate, Net       Floating Cage, Water Quality